Indonesia Problematic Internet Use Scale. (March 2019) - Andangsari, E W; Djunaidi, A; Fitriana, E; Harding, D
Abstract: Problematic Internet Use (PIU) is considered not to have consensus related to theory and assessment to date. The Indonesia Problematic Internet Use (IPIUS) is an instrument developed based on the Davis PIU concept and the modification of the GPIUS2 Caplan instrument. IPUS consists of 63 items with 6 dimensions, namely Preference of Online Social Interaction (POSI), escaping, cognitive preoccupation, compulsive internet use, negative outcomes, and emotional reactivity. The emotional reactivity dimension is deemed necessary in IPIUS to consider the emotional problems that arise in internet use in Indonesia. The CFA test results indicate that IPIUS is a valid model and fit well with the data and it is valid to be applied for further research.